Human Circulating MicroRNA-1 and MicroRNA-126 as Potential Novel Indicators for Acute Myocardial Infarction - Long, Guangwen (Ivyspring International Publisher, 2012)
Circulating miRNAs have been shown as promising biomarkers for various pathologic conditions. The aim of this study was to clarify that circulating miR-1 and miR-126 in human plasma might be useful as biomarkers in acute myocardial infarction (AMI). In our study, after pre-test, two candidate miRNAs were detected by using real-time RT-PCR. Cardiac troponin I (cTnI) concentrations were measured by ELISA assay in plasma from patients with AMI (n=17) and healthy subjects (n=25), simultaneously. Increased miR-1 and decreased miR-126 in plasma from patients with AMI after the onset of symptoms compared with healthy subjects were found. A remarkable finding in this study is that miR-1, miR-126 and cTnI expression levels exhibited the same trend. Our results suggest that the plasma concentrations of miR-1 and miR-126 may be useful indicators for AMI.